The rational design of Ni3S2 nanosheets–Ag nanorods on Ni foam with improved hydrogen adsorption sites for the hydrogen evolution reaction. Issue 13 (11th June 2021) - Liu, Hai-Jun; Yu, Wen-Li; Li, Meng-Xuan; Dou, Shu-Yue; Wang, Fu-Li; Fan, Ruo-Yao; Ma, Yu; Zhou, Yu-Lu; Chai, Yong-Ming; Dong, Bin
Abstract : Heterostructures made of Ni3 S2 nanosheets–Ag nanorods on Ni foam are rationally designed as efficient electrocatalysts for the HER under alkaline conditions. Abstract : Transition-metal sulfides (M x S y ) have attracted great interest as promising catalysts for the hydrogen evolution reaction (HER) due to their low cost. However, the formation of sulfur–hydrogen bonds on M x S y (S–Hads ) severely suppresses the HER. In this paper, we report a three-dimensional nickel sulfide (Ni3 S2 ) film supported by Ag nanorods (NRs) on Ni foam (Ni3 S2 –Ag/NF) as a type of electrocatalyst for the HER in alkaline media. The tight coupling between Ag and Ni3 S2 creates a mass of heterojunctions. Therefore, this electrocatalyst only shows a low overpotential of 161 mV at 10 mA cm −2, as well as satisfactory stability for 10 h. Density functional theory calculations reveal that the intense electronic interactions in the heterojunctions of the Ni3 S2 –Ag hybrids can facilitate water adsorption and activation, improve H-adsorption and desorption on the electrocatalysts, and reduce the formation of S–Hads bonds on the catalyst surfaces. The existence of strong interactions between Ag and Ni3 S2 in the electrocatalyst can facilitate both the Volmer and Heyrovsky steps of the HER and cause the Ni3 S2 –Ag/NF electrocatalysts to exhibit outstanding HER catalytic performance. This suitable strategy involving Ag doping may be a promising choice for developing Ni sulfide-based electrocatalysts for the HER.